Analisis Self Presenting Remaja di Media Sosial: Analysis of Teenagers Self-Presenting on Social Media - Umi Kulsum; Bukhori, Imam; Winarsih, Nining (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) UIN Datokarama Palu, 2024)
This study examines how adolescents engage in self-presentation on social media. The research employs a qualitative approach. Data collection techniques include observation, interviews, and documentation. The validity of the data is ensured through triangulation techniques, specifically method triangulation and source triangulation. The results show that adolescents in Gebangan Village, particularly those from middle-class families, tend to present themselves in roles of social climbing within the realms of motivators and socialites for reasons of happiness, enjoyment, and entertainment, both for themselves and for the media. This behavior is adopted to adapt and avoid feeling left behind, as well as to positively increase followers or friendships. Additionally, it was found that adolescents often use social media as a means to seek social validation and support from peers. This study provides new insights into adolescent behavior on social media and makes a significant contribution to understanding how social media influences the construction of social identity among adolescents. These findings can serve as a basis for further research on the psychological impact of self-presentation on social media and its influence on adolescent identity formation.